Synthesis and biological evaluation of phosphatidylcholines with cinnamic and 3-methoxycinnamic acids with potent antiproliferative activity. Issue 62 (19th October 2018) - Czarnecka, Marta; Świtalska, Marta; Wietrzyk, Joanna; Maciejewska, Gabriela; Gliszczyńska, Anna
Abstract : A series of eight novel phosphatidylcholines containing CA or 3-OMe-CA acids (3a-b, 5a-b, 9a-b, 10a-b ) at sn -1 and/or sn -2 positions were synthesized and tested for their antiproliferative activity against selected cancer cell lines. Abstract : A series of eight novel phosphatidylcholines containing cinnamic or 3-methoxycinnamic acids (3a-b, 5a-b, 9a-b, 10a-b ) at sn -1 and/or sn -2 positions were synthesized and tested for their antiproliferative activity in an in vitro model against representative six human cancer cell lines (MV4-11, A549, MCF-7, LoVo, LoVo/DX, HepG2) and a normal cell line BALB/3T3. The structures of the new compounds were confirmed by spectral analysis. Biological evaluation revealed that all the tested conjugates exhibited higher antitumor activity than the corresponding free aromatic acids. Compounds3b and9b turned out to be the most active, with IC50 values of 32.1 and 30.5 μM against the LoVo/DX and MV4-11 cell lines, respectively. Studies of the mechanism of the antitumor action were carried out for 1-palmitoyl-2-cinnamoyl- sn -glycero-3-phosphocholine (5a ), and it was shown to be active toward almost all the tested types of cancer cells, showing that this compound could effectively arrest the cell cycle in G2/M and decrease the mitochondrial membrane potential of leukemia MV4-11 cells. The obtained results proved that the strategy of the incorporation of cinnamic and 3-methoxycinnamic acids into phospholipids could expand their potential application in industry, as well as could improve their antiproliferative activity and selectivity toward cancer cell lines.